2010
DOI: 10.1152/ajprenal.00126.2010
|View full text |Cite
|
Sign up to set email alerts
|

Excess diuresis and natriuresis during acute sleep deprivation in healthy adults

Abstract: The transition from wakefulness to sleep is associated with a pronounced decline in diuresis, a necessary physiological process that allows uninterrupted sleep. The aim of this study was to assess the effect of acute sleep deprivation (SD) on urine output and renal water, sodium, and solute handling in healthy young volunteers. Twenty young adults (10 male) were recruited for two 24-h studies under standardized dietary conditions. During one of the two admissions, subjects were deprived of sleep. Urine output,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 45 publications
(41 reference statements)
3
77
1
1
Order By: Relevance
“…Although the direct renal effects of aberrant sleep duration have not been extensively investigated, emerging evidence suggests that sleep deprivation could interfere with normal renal physiology. Acute sleep deprivation in humans reduces plasma renin, angiotensin, and aldosterone levels, and is associated with increased urinary excretion of sodium and potassium [20,21]. In addition, the normal nocturnal dipping of blood pressure is attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct renal effects of aberrant sleep duration have not been extensively investigated, emerging evidence suggests that sleep deprivation could interfere with normal renal physiology. Acute sleep deprivation in humans reduces plasma renin, angiotensin, and aldosterone levels, and is associated with increased urinary excretion of sodium and potassium [20,21]. In addition, the normal nocturnal dipping of blood pressure is attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Middelkoop et al reported that the most frequent subjective cause of disturbed sleep maintenance is nocturia (67.5%), 51 and Bliwise et al reported that nocturia is an independent predictor of selfreported insomnia and reduced sleep quality. 52 In contrast, excessive diuresis and natriuresis during the night are induced by acute sleep deprivation, as shown by Kamperis et al 102 While the cause or effect is unclear, several epidemiological studies have shown a correlation of insomnia/ poor sleep to nocturia. 14,26,76,103 As well as sleep quality, duration of sleep is associated with the number of nocturia episodes.…”
Section: Sleep (Insomnia Osas)mentioning
confidence: 99%
“…For instance, Kamperis et al have shown that acute sleep deprivation in humans leads to excessive natriuresis and kaliuresis during the subjective night and attenuation of the nocturnal BP dip. 8 Numerous studies have demonstrated an impairment of the sodium excretory rhythm and the development of hypertension in shift workers. 9,10 The circadian clock can influence renal function via two types of circadian inputs: (1) entrainment of renal rhythms through the external circadian time cues, such as hormones, food, activity, and body temperature rhythms, and (2) the activity of the intrinsic renal circadian clock.…”
mentioning
confidence: 99%